IMPLENTASI KEBIJAKAN SD-SMP NEGERI 4 SATU ATAP DI DESA PONGKAR KECAMATAN TEBING KABUPATEN KARIMUN - Sawirdi Sawirdi (LPPM Universitas Terbuka, 2016)
The study aims to describe and analyze the implementation of ‘two schools under one-roof’policy which integrate primary and secondary schools in Pongkar Village, Tebing, Karimun District. The research informants consists the principals, teachers, administrative staff, school committees, and students at the Under One roof schools at Pongkar Village, and of the officials of the Karimun District Education Office. Methods of data collection are interview, observation and documentation study. The results showed that the policy of one-roof SD-SMPN 4 in Pongkar Village has been run in accordance with the objectives of its establishment, indicated from the standard and the policy objectives that have been achieved, the inter-organization communications went smoothly, and the activities to ensure the implementation of the policy went well. Conducive socio-economic and political conditions support the implementation of the under-one-roof school policy. Inhibiting factors that occur are insufficient facilities and infrastructure, the insufficient number of teachers, low motivation of some communities to send their children to this school, and geographical conditions. Attempts to overcome obstacles in implementing the policy includes obtaining special funding assistance from the Karimun District Education Office, empowering teachers to make learning more effective, better arranging school schedules, and socializing the policy and the school to the community. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis: (1) pelaksanaan kebijakan SD-SMP satu atap di Desa Pongkar Kecamatan Tebing. Informan penelitian adalah pejabat Dinas Pendidikan Kabupaten Karimun, kepala sekolah, guru, pegawai tata usaha, komite sekolah, dan siswa. Lokasi penelitian di sekolah satu atap di Desa Pongkar Kecamatan Tebing Kabupaten Karimun. Metode pengumpulan data dengan wawancara, observasi dan studi dokumentasi. Hasil penelitian menunjukkan bahwa kebijakan SD-SMPN 4 satu atap di Desa Pongkar telah berjalan sesuai dengan tujuan pendiriannya, terlihat dari standar dan tujuan kebijakan yang telah tercapai, komunikasi interorganisasi berjalan dengan lancar, dan aktifitas pengukuhan berjalan dengan baik. Kondisi sosial ekonomi dan politik yang kondusif mendukung pelaksanaan sekolah satu atap. Faktor-faktor penghambat yang terjadi adalah sarana dan prasarana yang belum memadai, jumlah tenaga pendidik dan kependidikan belum cukup, motivasi sebagian masyarakat untuk menyekolahkan anaknya masih rendah, serta kondisi geografis. Usaha untuk mengatasi hambatan dalam pelaksanaan kebijakan SD-SMP Negeri 4 satu atap di antaranya adalah memperoleh bantuan dana khusus dari Dinas Pendidikan Kabupaten Karimun, memberdayakan guru-guru agar pembelajaran lebih efektif, pengaturan jadwal sekolah yang lebih baik, dan melakukan sosialisasi kepada masyarakat.